Watching over you - Foster, Lori, 1958- (Foster, Lori, 1958- McKenzies of Ridge Trail., 2021)
"While investigating a criminal network, Detective Crosby Albertson keeps crossing paths with members of the highly trained, suspiciously well-informed McKenzie family... Madison McKenzie is the tech and surveillance whiz of her family's operation. A recent case introduced her to Detective Albertson. She finds herself irresistibly drawn to the sexy and mysterious cop. There's just one problem. He's a detective and her family's work is secret"--